PENGEMBANGAN MEDIA PEMBELAJARAN MODUL FISIKA BERBASIS CETAKAN (MFBC) PADA MATERI SUHU DAN KALOR - Eka Prastia; I Dewa Putu Nyeneng; Agus Suyatna (Jurnal Pembelajaran Fisika, 2013)
A module is a lesson material presented systematically with understandablelanguage for students according to their ability and knowledge levels, so that thestudents will be able to learn autonomously with or without teacher assistances.However, there is no module in State Junior High School 20 in Bandar Lampungthat is in accordance with grade-based curriculum (or KTSP) 2006. Therefore, amodule that is able to improve student’s autonomous learning is required todevelop. The learning media development design of printed-based physic module(or MFBC) is adapted from instructional media development process by Sadiman(2008) as the reference that consists of need analysis of development program,development design, product development, and product evaluation, producttesting and product printing. This evaluation consists of formative evaluation I,formative evaluation II, formative evaluation III. In material test by experts, thescore was 2,8 and this belonged to good category. The second evaluation, thedesign test by experts, the score was 2,9. This score belonged to good categoryand was in accordance with BSNP standard. The third evaluation was on-on-onetest that was conducted to three students from different classrooms (classroomVIID, VIIE and VIIG) and the score was 3,63. It belonged to good category. The lasttest was field test to find out the effectiveness and attractiveness of the module.Field test was conducted to 36 students in VIIE classroom in State Junior HighSchool 20 in Bandar Lampung. The effectiveness test result showed 77,7%student accomplished the material and they got average marks of 74,07, and itwas above the minimum criteria of accomplishment (or KKM). Attractiveness,easiness, and benefit tests were conducted to students who experienced learningusing developed module by giving them questionnaires. The results showed thatthe developed module was very interesting, very easy and very beneficial.Keywords: development research, learning media, printed-based media, module